Ganglioglial differentiation in a medulloblastoma with extensive nodularity - Bruna Ferreira Bernert; Alex Roman; Paulo Carboni Jr; Luiz Fernando Bleggi Torres (Sociedade Brasileira de Patologia Clínica, 2013)
We report the case of a 2 month-old patient with a large, probably congenital, posterior fossa tumor. Hematoxylin and eosin staining (HE), reticulin and immunohistochemistry revealed a medulloblastoma with extensive nodularity, showing ganglioglial differentiation, high proliferative index in the primitive neuroectodermal tumor (PNET) area and low proliferative index in the ganglioglial maturation area. Ganglioglial differentiation is a rare event in medulloblastomas and its mechanism is still unknown. Previous surgery, radiation and chemotherapy may contribute to differentiation in astrocytic and nerve cells. In this case, however, the differentiation was already present in the first specimen, prior to any surgical or therapeutic procedure.